Analysis to Reduce Ship Accidents in Indonesia through the Ship Safety Management and Regulatory Compliance Approach - Mochamad Furqon Rochyana; Nandan Limakrisna; Prasadja Ricardianto; Datep Purwa Saputra (Green Publisher, 2025)
This study examines the implementation of ship safety management in Indonesia, identifies the factors contributing to ship accidents, and evaluates the effectiveness of existing maritime safety regulations. Using a qualitative approach through in-depth interviews, field observations, and document analysis, the research aims to formulate strategic recommendations to improve maritime safety in Indonesian waters. The findings indicate a gap between regulations and their implementation, inadequate training, and challenges in law enforcement. The proposed recommendations include enhancing training programs, strengthening supervision, and adopting the latest safety technologies.